Tinjauan Atas Pelaporan Keuangan Organisasi Sektor Publik Studi Kasus: RSJ Soeharto Heerjan 2010-2013 - Hendra F Santoso (Jurnal Akuntansi, 2014)
ABSTRACTThe public sector concerned with providing basic government services, as the police, military, public roads, public transit, primary education and health care for the poor. The public sector organization can be one of two types either funded directly by the government or publicly owned where a majority of the organization’s shares are owned by the government. A hospital is a health care institution providing patient treatment with specialized staff and equipment. A mental hospital is a hospital for mentally incompetent or unbalanced person. Hospital administrations are individuals or groups of people who act as the central point of control within hospitals. There are two types of administrators, generalists and specialists. Generalist are individuals who are responsible for managing or helping to manage an entire facility. Specialist are individuals who are responsible for efficient operations or specific department such as policy analysis, finance, budgeting, accounting etc. Accounting is the system of recording and summarizing business and financial transactions and analyzing, verifying and reporting the result . According Encyclopedia of accounting systems, three reports of a hospital will include a balance sheet, a statement of activity, and a cash flows statement at the minimum. The object of this study is the financial statements RSJ Soeharto Heerjan. This study uses descriptive method where information collected through webside RSJ Soeharto Heerjan and RSJ Soeharto Heerjan. The purpose of this study is to know the financial reporting RSJ Soeharto Heerjan 2010-2013. Result of this study showed that the report has been made of RSJ Soeharto Heerjan are Statement of Budget Realization, Balance Sheet, Statement of Activity, Cash Flows Statement and Notes to the Financial Statements and Performance Reports. Based on the results of the review, the report RSJ Dr. Soeharto Heerdjan has implemented Government Accounting Standards showed through Statement of Budget Realization and Performance Reports. RSJ Dr. Soeharto Heerjan has implemented Statement of Financial Accounting Standards No 45 showed through Balance Sheet, Statement of Activity, Cash Flows Statement and Notes to Financial Statements.Keywords: The Public Sector, A Hospital, The Financial Reporting, GAS, FAS No 45